Relationship between OAEs and Behavioural Discrimination Ability of Normal Hearing Individuals - Varun Uthappa; Priyanka Shailat; Animesh Barman (Journal of All India Institute of Speech and Hearing, 2010)
Frequency selectivity and Otoacoustic emissions (OAEs) have been shown to exhibit some relationship, which may explain the psychoacoustics of the ear on peripheral testing. The current study attempts to find the relationship between the amplitudes of OAE and frequency discrimination abilities across frequencies within an individual. The amplitudes of Transient Evoked Otoacoustic Emissions (TEOAE) (signal to noise ratio - SNR), TEOAE (absolute amplitudes) and Distortion Product Otoacoustic Emissions (DPOAE) were measured at 1, 1.5, 2, 3 and 4 kHz respectively in ten ears with normal hearing. Difference Limen for Frequency (DLF) and Frequency Modulated Difference Limen (FMDL) were measured at ten and forty dBSL at the frequencies at which maximum and minimum TEOAE / DPOAE amplitudes were obtained. The difference limens were compared across the frequencies at which maximum and minimum TEOAE / DPOAE amplitudes were obtained. There was no significant difference between frequency discrimination abilities at frequencies with maximum and minimum OAE amplitudes. The results showed that within an individual, the OAE amplitudes might not give information regarding the frequency discrimination abilities. The OAE amplitude not only depends on the status of the outer hair cells. The amplitude also varies with several other factors like the resonance properties of the middle and external ears. Hence, no one to one correlation was obtained. OAEs may not give reliable measures to draw information about the behavioral discrimination ability of individuals.